PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIIE SMP NEGERI 1 SIAK HULU - Rice Aldes Ginanti; Sehatta Saragih; Suhermi Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is classroom action research that aims to improve learning process and to increase mathematics achievement with applied the learning cooperative approach Think Pair Share (TPS) model. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection.The subject of this research is student of class VIIIE SMPN 1 Siak Hulu in academic years 2018/2019, which amounted to 32 students, consist of 15 boys and 17 girls. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students Mathematic tests were analyzed in quantitative descriptive. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. Most of students were very confidenced and actived in learning process, such as while they were finished mathematic’s problems that given, presenting the result of problems and giving the conclusion of learning. Number of students that reach Minimum Mastery Criteria increase from basic score to first test I and II. The results of this research showed an increasing number of students learning mathematics about knowledge of the basic score (37,5%) to the first test (46,9%) to the second test II (68,75%). Results of this research indicates that appication of the learning cooperative approach Think Pair Share (TPS) model can improve learning process and increase mathematics achievement from the students at class VIIIE SMPN 1 Siak Hulu in academic years 2018/2019 for the subject matter of Flat Side Space.Key Words: Mathematics Achievement, Learning Cooprative Approach Think Pair Share (TPS), Classroom Action Research